Periorbital Necrotizing Fasciitis: A Case Report - Köhle, Ülkü; Yılmaz, Turgut; Yıldırım, A. Mustafa; Okur, M. İhsan; Kükner, Şahap (Fırat University, 2003)
Periorbital necrotizing fasciitis is a soft tissue enfection, usually polymicrobial, characterised by necrosis of fascia and subcutaneous tissue. It frequently involves the groin, abdomen and extremities, but rarely involves the fascial region. In this article a case is presented of a 57-year-old woman who following a kick of cow developed a periorbital necrotising fasciitis. Bacteriological investigations revealed the presence of Streptococcus pyogenes. The virulence of this microorganism requires an aggressive approach to the patient with periorbital necrotizing fasciitis, which is refractory to intravenous antibiotics. Early treatment may limit extensive eyelid necrosis, the resultant secondary deformity, and the need for multiple reconstructive procedures.

Nekrotizan fassiit, fasya ve cilt altı dokunun nekrozu ile karakterize, genellikle birden fazla mikroorganizmanın sebep olduğu bir yumuşak doku enfeksiyonudur. İnguinal bölge, karın ve ekstremitelerde sık görülmesine karşılık nadiren yüz bölgesinde de rastlanır. Bu çalışmada 57 yaşındaki bir kadın hastada inek tepmesinden sonra periorbital nekrotizan fassiit oluşumu sunulmuştur. Yapılan bakteriyolojik çalışmalarda streptococcus pyogenes izole edildi. İntravenöz antibiyotiklere dirençli olan periorbital nekrotizan fassiitli hastalarda bu mikroorganizmanın virülansı nedeniyle agressif yaklaşım gereklidir. Erken tedavi göz kapağındaki nekrozun artmasını, sekonder deformite oluşumunu ve birçok rekonstrüktif girişime olan ihtiyacı azaltır.
Periorbital Nekrotizan Fassiit: Olgu Sunumu